Middle East versus Saharan dust extinction-to-backscatter ratios - Nisantzi, Argyro; Mamouri, Rodanthi-Elisavet; Ansmann, Albert; Schuster, G. L.; Hadjimitsis, Diofantos G. (My University, 2015)
Four years (2010–2013) of observations with polarization lidar and sun/sky photometer at the combined European Aerosol Research Lidar Network (EARLINET) and Aerosol Robotic Network (AERONET) site of Limassol (34.7° N, 33° E), Cyprus, were used to compare extinction-to-backscatter ratios (lidar ratios) for desert dust from Middle East deserts and the Sahara. In an earlier article, we analyzed one case only and found comparably low lidar ratios < 40 sr for Middle East dust. The complex data analysis scheme is presented. The quality of the retrieval is checked within a case study by comparing the results with respective Raman lidar solutions for particle backscatter, extinction, and lidar ratio. The applied combined lidar/photometer retrievals corroborate recent findings regarding the difference between Middle East and Saharan dust lidar ratios. We found values from 43–65 sr with a mean (±standard deviation) of 53 ± 6 sr for Saharan dust and from 33–48 sr with a mean of 41 ± 4 sr for Middle East dust for the wavelength of 532 nm. The presented data analysis, however, also demonstrates the difficulties in identifying the optical properties of dust even during outbreak situations in the presence of complex aerosol mixtures of desert dust, marine particles, fire smoke, and anthropogenic haze.
Keywords: Middle East; Saharan; Dust extinction; EARLINET; AERONET